Beschuldigtennationalität und polizeiliche Ermittlungspraxis: Plädoyer für eine qualitative Polizeiforschung = The nationality of suspected persons and investigations by police: a plea for the use of qualitative research methods - Reichertz, Jo (1993)
Though relevant more nongerman juvenile and young persons than german ones are suspected of having offended against the law, the risk for the nongermans of being sentenced is relevant smaller. It is hypothesized that this phenomenon does not result from a different 'criminal disposition' of german and nongerman juvenile and young persons, but from the different kind of inquiry and examination by the police for the two groups of people. To clear up this phenomenon further, it seems not to be adequate to analyze only offense statistics, but to use qualitative research methods.